Saudi Higher Education Accreditation: From Policy to Practice: Cultural Inquiry into Saudi Academics’ Practices During the Implementation of Accreditation Standards - Aljendan , Aisha Yousef (Journal of Ecohumanism, 2024)
This paper investigates the relationships between Saudi cultural factors and the practices associated with the implementation of accreditation standards in Saudi higher education institutions (HEIs). Through a qualitative study involving document analysis, interviews, and observations, data was collected from a sample of 33 academic leaders and faculty members at three Saudi universities. The findings reveal a strong correlation between cultural elements and the practices of Saudi academics during the accreditation process. Using a social practice theory (SPT) approach, the study demonstrates how cultural issues influence common practices and actions, highlighting the integration of Saudi identity, traditions, and contemporary values in the implementation methods. The research underscores the importance of cultural awareness in addressing the gap between policy and practice, suggesting that modifications to accreditation guidelines should consider these cultural factors. The study also discusses the positive impact of recent educational reforms and the empowerment of women in supporting the accreditation process. These insights aim to enhance the effectiveness of accreditation efforts in Saudi Arabia, ensuring they meet international standards while respecting the local cultural context.